Anti Müllerian Hormone as a Predictor of Metabolic Syndrome in Polycystic Ovary Syndrome - Wiweko, Budi; Susanto, Cynthia A. (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To evaluate whether Anti Müllerian Hormone (AMH) can be used as a predictor of metabolic syndrome in Polycystic Ovarian Syndrome (PCOS).Methods: This cross-sectional study was conducted in Yasmin Clinic, Dr. Cipto Mangunkusumo General Hospital Jakarta between June and December 2012. Forty-one patients diagnosed with PCOSbased on Rotterdam Criteria were enrolled. Secondary were was taken from medical record..Results: A total of 22 subjects were involved in this study. Mean AMH level in the metabolic syndrome group is compared to the non-metabolic syndrome group (10.72 ± 6.23 ng/ml vs 7.97 ± 4.50ng/ml, p=0.12). AMH was strongly associated with HDL, triglyceride and insulin resistance (r-value of -0.29, 0.23, and 0.21 respectively, p < 0.05).Conclusion: AMH can be used as a predictor of metabolic syndrome in PCOS.[Indones J Obstet Gynecol 2017; 5-2: 83-86]Keywords: anti müllerian hormone, metabolic syndrome, polycystic ovarian syndrome